2010
DOI: 10.1007/s00284-010-9637-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bombyx mori Nucleopolyhedrovirus ORF109 that Encodes a 25-kDa Structural Protein of the Occlusion-Derived Virion

Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) ORF109 (Bm109) is a gene present in many lepidopteran NPVs, but its function is unknown. In this study, Bm109 was characterized. The transcript of Bm109 was detected at 12-72 h postinfection (p.i.). Polyclonal antiserum raised to a His-BM109 fusion protein recognized BM109 in infected cell lysates from 24 to 72 h p.i., suggesting that Bm109 is a late gene. Localization of the BM109 in BV and ODV by western analyses demonstrated that BM109 was proteins of ODV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…AcMNPV P24 (Ac129) and its homolog in OpMNPV are located to both BVs and ODVs (Wolgamot et al 1993), while its homolog in Spodoptera litura NPV (SpliNPV) is only associated with ODVs (Li et al 2005b). Additionaly, AcMNPV Ac66 and Ac132 are located to BVs (Ke et al 2008;Yang et al 2014), while their homologs in BmNPV were not found to be associated with BVs (Zhou et al 2010). Immunogold-labeled P48 was localized to the plasma membrane, nuclear envelope, intranuclear microvesicles, nucleocapsids in the VS, and the envelope and nucleocapsid of ODVs in virus-infected cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AcMNPV P24 (Ac129) and its homolog in OpMNPV are located to both BVs and ODVs (Wolgamot et al 1993), while its homolog in Spodoptera litura NPV (SpliNPV) is only associated with ODVs (Li et al 2005b). Additionaly, AcMNPV Ac66 and Ac132 are located to BVs (Ke et al 2008;Yang et al 2014), while their homologs in BmNPV were not found to be associated with BVs (Zhou et al 2010). Immunogold-labeled P48 was localized to the plasma membrane, nuclear envelope, intranuclear microvesicles, nucleocapsids in the VS, and the envelope and nucleocapsid of ODVs in virus-infected cells (Fig.…”
Section: Discussionmentioning
confidence: 99%